SYSTEM CONSOLIDATED SALES OF PRODUCTS PT.ALPINA - Bambang Sigit Kamseno; Sahni Damerianta Purba, S.kom, MM (Jurnal Sistem Informasi, 2002)
In product sales Alpina products will provide excellent results. This is due to the use of computerized systems at the company that will make the results obtained will have a small miscalculation and will increase company profits.Computerized system which will be built very profitable companies, therefore the existing system should be able to keep abreast of the times and can solve problems - problems that arise because of errors from manual calculation. With the computerized system is expected to make in preparation of reports as well as speed up the decision to assign the decision to further policy making.